Development of GBTS and KASP Panels for Genetic Diversity, Population Structure, and Fingerprinting of a Large Collection of Broccoli (Brassica oleracea L. var. italica) in China - Shen, Yusen; Wang, Jiansheng; Shaw, Ranjan K.; Yu, Huifang; Sheng, Xiaoguang; Zhao, Zhenqing; Li, Sujuan; Gu, Honghui (Frontiers in Plant Science, 2021)
Broccoli (Brassica oleracea var. italica) is one of the most important and nutritious vegetables widely cultivated in China. In recent four decades, several improved varieties were bred and developed by Chinese breeders. However, the efforts for improvement of broccoli are hindered by limited information of genetic diversity and genetic relatedness contained within the available germplasms. This study evaluated the genetic diversity, genetic relationship, population structure and fingerprinting of 372 accessions of broccoli representing most of the variability of broccoli in China. Millions of SNPs were identified by whole genome sequencing of 23 representative broccoli genotypes. Through several stringent selection criteria, a total of 1,167 SNPs were selected to characterize genetic diversity and population structure. Of these markers, 1,067 SNPs were genotyped by target sequencing (GBTS) and 100 SNPs were genotyped by kompetitive allele specific PCR (KASP) assay. The average polymorphism information content (PIC) and expected heterozygosity (gene diversity) values were 0.33 and 0.42 respectively. Diversity analysis revealed the prevalence of low to moderate genetic diversity in the broccoli accessions indicating a narrow genetic base. Phylogenetic and principal component analyses revealed that the 372 accessions could be clustered into two main groups but with weak groupings. STRUCTURE analysis also suggested the presence of two subpopulations with weak genetic structure. Analysis of molecular variance (AMOVA) identified 13% variance among populations and 87% within populations revealing very low population differentiation which could be attributed to massive gene flow and the reproductive biology of the crop. Based on high resolving power, a set of 28 KASP markers was chosen for DNA fingerprinting of the broccoli accessions for seed authentication and varietal identification. To the best of our knowledge, this is the first comprehensive study to measure diversity and population structure of a large collection of broccoli in China and also the first application of GBTS and KASP techniques in genetic characterization of broccoli. This work broadens the understanding of diversity, phylogeny and population structure of a large collection of broccoli which may enhance future breeding efforts to achieve higher productivity.